The Credit Composition of Global Liquidity - Helmut Herwartz; Christian Ochsner; Hannes Rohloff (Philipps-University Marburg, School of Business and Economics, 2021)
We conceptualize global liquidity as global monetary policy and credit components by means of a large-scale dynamic factor model. Going beyond previous work, we decompose aggregate credit components into credit supply and demand flows directed at businesses, households and governments. We show that this decomposition enhances the understanding of global liquidity considerably. Whereas global government sector credit supply is best understood as a safe-haven lending factor from an investors perspective, lenders supply the businesses and households with credit to maximize profits along the financial cycle. Moreover, the government sector demands credit in times of bust-episodes, whereas private entities demand credit in times of booms. In particular, we find that our global credit estimates explain substantial variance shares of a large panel of international financial aggregates.
Keywords: C32; C38; E32; E44; E51; 330; global liquidity; credit composition; financial cycle; dynamic factor model